2018
DOI: 10.1111/apm.12879
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Campylobacter jejuni and Campylobacter coli water isolates in lake and well water

Abstract: The role of water for transmission of Campylobacter jejuni and C. coli to humans might be underestimated, as factors important for bacterial viability in water are largely unknown. We have studied water survival of seven C. jejuni and eight C. coli isolates originally isolated from Swedish waters, together with selected reference strains, over eight days at 4 °C in the dark in untreated water collected from a local lake and a private well. To study seasonality, lake water samples were collected during spring a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Twenty-one percent of the water samples were contaminated with diverse Campylobacter species. Several studies have assessed the prevalence of Campylobacter spp in different water sources [1,49,50,51]. In South Africa, 13% was reported in surface and groundwater [52], and in New Zealand, 75% and 29.2% were found in groundwater and drinking water, respectively [53].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-one percent of the water samples were contaminated with diverse Campylobacter species. Several studies have assessed the prevalence of Campylobacter spp in different water sources [1,49,50,51]. In South Africa, 13% was reported in surface and groundwater [52], and in New Zealand, 75% and 29.2% were found in groundwater and drinking water, respectively [53].…”
Section: Discussionmentioning
confidence: 99%
“…The highest Campylobacter contamination in the present study was found in water samples collected from stored containers (rainwater, well and municipal taps). Several factors have been linked to the poor microbial quality of stored household water [50]. Although treated municipal water may contain residual chlorine to ensure the safety of the water during storage, prolonged storage within the house could lead to recontamination of the water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have suggested that although Campylobacter spp. are extremely sensitive to various stress conditions, C. jejuni can survive in various types of environments by forming biofilms [ 23 , 24 ] and can protect itself from chemical products, physical cleaning processes, and other types of environmental stress [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In New Zealand, consumption of untreated water was the third most reported risk factor associated with campylobacteriosis in 2015 (ESR, ). Campylobacter can survive in water for up to several months, depending on environmental conditions and on the strain (Rollins and Colwell, ; Korhonen and Martikainen, ; Chan et al, ; Obiri‐Danso et al, ; Cools et al, ; Trigui et al, ; Nilsson et al, ). An important survival strategy for Campylobacter is to form or integrate into biofilms, which enables the micro‐organism to survive in environments where it would normally perish.…”
Section: Introductionmentioning
confidence: 99%